2009
DOI: 10.1200/jco.2008.18.7948
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Stratified Therapy and the Intensive Use of Cytarabine Improves the Outcome in Childhood Acute Myeloid Leukemia: The AML99 Trial From the Japanese Childhood AML Cooperative Study Group

Abstract: A high survival rate, 75.6% at 5 years, was achieved for childhood with de novo AML in the AML99 trial. The treatment strategy was well tolerated with only 1.7% induction death rate and 3.5% remission death rate. Low-risk children were successfully treated with chemotherapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
190
7
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(204 citation statements)
references
References 27 publications
6
190
7
1
Order By: Relevance
“…In SR patients, however, a benefit of allo-SCT was found in some studies, and the meta-analysis on CCG, POG, and MRC AML 10 studies by Horan et al 9 reported a significant benefit in DFS and OS for SR patients treated with allo-SCT. Tsukimoto et al 31 found this benefit only for DFS but not for OS in the Japanese study, whereas in the United Kingdom Medical Research Council AML trials no benefit was found at all. It remains an open question whether SR patients benefit from allo-SCT in this time of effective chemotherapy, and this requires further clinical research, especially to determine which patients, if any, within this group will actually benefit from allo-SCT.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In SR patients, however, a benefit of allo-SCT was found in some studies, and the meta-analysis on CCG, POG, and MRC AML 10 studies by Horan et al 9 reported a significant benefit in DFS and OS for SR patients treated with allo-SCT. Tsukimoto et al 31 found this benefit only for DFS but not for OS in the Japanese study, whereas in the United Kingdom Medical Research Council AML trials no benefit was found at all. It remains an open question whether SR patients benefit from allo-SCT in this time of effective chemotherapy, and this requires further clinical research, especially to determine which patients, if any, within this group will actually benefit from allo-SCT.…”
Section: Discussionmentioning
confidence: 98%
“…The 5-year OS of 16 HR patients who underwent allo-SCT (6 related SCT, 6 unrelated SCT, and 4 cord blood SCT) was 69%. 31 …”
Section: Japanmentioning
confidence: 99%
“…11,[20][21][22] Data on the benefit of allo-HSCT in AMKL are conflicting. [1][2][3]10 We found no benefit of allo-HSCT in first CR, although criteria for allo-HSCT differed among protocols.…”
Section: Discussionmentioning
confidence: 99%
“…23 For example, the Japanese Childhood AML Cooperative Study Group reported recently a 5-year survival of 86% Ϯ 6% and EFS of 71% Ϯ 8% for low-risk patients, which mainly included patients with t(8;21) on the AML99 trial. 24 These patients were treated with 5 consolidation courses, including cytarabine with a dosage up to 3 g/m 2 . Similarly, the 7-year survival for CBF-AML patients [18 patients with t(8;21) and 10 patients with inv(16)] on the AML-93 trial of the Nordic Society for Paediatric Hematology and Oncology was 77% Ϯ 10%, using a regimen including 4 courses of HDAC-based therapy.…”
Section: Discussionmentioning
confidence: 99%